Education for Wonder - Haydn Washington (MDPI AG, 2018)
This article argues that rejuvenating a sense of wonder towards nature is essential to ecocentric education and to finding a sustainable future. It examines the barriers that block education for wonder and looks at the issues around education for wonder in the home, at school, at university, and in the community in general. It considers the scale of a natural area in terms of wonder education, and ways of teaching wonder in school that increase wonder rather than isolate the student from nature. It also considers the issue of an “education for sustainable development” influenced by anthropocentrism, in contrast to an environmental education where some scholars accept the intrinsic value of nature. It discusses the need to balance “facts” in education with ethics. The article concludes by summarizing the steps needed to re-educate for wonder.